Developing Digital English-Learning Supplementary Media for Students of Islamic Studies - Fakhrurriana, Ria; Ningsih, Wety Asri (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
As English is massively learned, it becomes one of compulsory subject in university level. However, it can be a problem for EFL (English as Foreign Language) learners of ESP (English for Specific Purposes), such the students of Islamic studies. Therefore, students need more learning sources that can be easily accessed to facilitate them study English. This study intends to develop English supplementary media for students of Islamic studies. This study is conducted qualitatively using Research and Development design and applies ADDIE: analysis, design, development, implementation, and evaluation as research model. The participants of this study are 35 second semester students of Islamic studies in Tarbiyah Faculty, IAIN Kediri. The researchers used questionnaire to collect information about what English skill students need to learn as students of Islamic studies. Furthermore, the researchers designed and developed the media according to the result of preliminary study. Then, the media is validated by experts using prepared validation sheet. To ensure its effectiveness and to find out students' response towards this media, the researches implemented the developed media to the students. In the end, students show positive response towards the developed media. This media is expected to be used extensively by early year students of Islamic study.